Comparative analyses of Linderniaceae plastomes, with implications for its phylogeny and evolution - Yan, Rongrong; Geng, Yanfei; Jia, Yuhuan; Xiang, Chunlei; Zhou, Xinxin; Hu, Guoxiong (Frontiers in Plant Science, 2023)
Introduction The recently established Linderniaceae, separated from the traditionally defined Scrophulariaceae, is a taxonomically complicated family. Although previous phylogenetic studies based on a few short DNA markers have made great contributions to the taxonomy of Linderniaceae, limited sampling and low resolution of the phylogenetic tree have failed to resolve controversies between some generic circumscriptions. The plastid genome exhibits a powerful ability to solve phylogenetic relationships ranging from shallow to deep taxonomic levels. To date, no plastid phylogenomic studies have been carried out in Linderniaceae. Methods In this study, we newly sequenced 26 plastid genomes of Linderniaceae, including eight genera and 25 species, to explore the phylogenetic relationships and genome evolution of the family through plastid phylogenomic and comparative genomic analyses. Results The plastid genome size of Linderniaceae ranged from 152,386 bp to 154,402 bp, exhibiting a typical quartile structure. All plastomes encoded 114 unique genes, comprising 80 protein-coding genes, 30 tRNA genes, and four rRNA genes. The inverted repeat regions were more conserved compared with the single-copy regions. A total of 1803 microsatellites and 1909 long sequence repeats were identified, and five hypervariable regions (petN-psbM, rps16-trnQ, rpl32-trnL, rpl32, and ycf1) were screened out. Most protein-coding genes were relatively conserved, with only the ycf2 gene found under positive selection in a few species. Phylogenomic analyses confirmed that Linderniaceae was a distinctive lineage and revealed that the presently circumscribed Vandellia and Torenia were non-monophyletic. Discussion Comparative analyses showed the Linderniaceae plastomes were highly conservative in terms of structure, gene order, and gene content. Combining morphological and molecular evidence, we supported the newly established Yamazakia separating from Vandellia and the monotypic Picria as a separate genus. These findings provide further evidence to recognize the phylogenetic relationships among Linderniaceae and new insights into the evolution of the plastid genomes.